Examining shared monitoring in collaborative learning: A case of a recurrence quantification analysis approach - Dindar, Muhterem; Alikhani, Iman; Malmberg, Jonna; Järvelä, Sanna; Seppänen, Tapio (Computers in human behavior, 2019)
The aim of this study is to investigate the relationship between shared monitoring of collaborative learning processes and physiological synchrony between the collaborating group members. Shared monitoring fuels collaborative learning in groups. Video and electrodermal activity data were collected from a group of high school students (two male, one female) during two sessions of collaborative learning. Shared monitoring of learning progress among the group members, in terms of frequency and duration, were coded and calculated in video data. Physiological synchrony in electrodermal activity among the collaborating students was calculated with Multidimensional Recurrence Quantification Analysis (MdRQA). Results revealed that the relationship between physiological synchrony and shared monitoring might be dependent on task type. That is, a significant relationship was observed between MdRQA indices and shared monitoring in one session, whereas no significant relationship was observed in the other session. The current study contributes to the literature on computer-supported collaborative learning through demonstrating the utility of MdRQA to investigate the temporal dynamicity of collaborative learning processes. In conclusion, the chosen methods contribute to research on collaborative learning, as capturing invisible physiological signals and matching them with visible instances of monitoring processes facilitates identification of critical moments in collaboration. •Regulation in collaborative learning is not a static aptitude but a dynamic process.•Process-oriented methods can help to capture dynamicity of collaborative work.•MdRQA is a promising method to capture physiological synchrony of collaborators.•The level of physiological synchrony might be related with regulation of learning.